Scaling And Morphologic Analyses Of Topsar DEMs: A Quantitative Characterisation Perspective - Tay, Lea Tien (2007)
Digital Elevation Models (DEMs) have been widely used for terrain analysis and characterisation. With advent of Synthetic Aperture Radar (SAR) interferometry techniques, DEMs with fine resolution and high accuracy are made available. Motivated by the availability of this remarkable DEM, the terrain properties are analysed by proposing new scaling laws and roughness related indices in this research work. The study areas are part of Cameron Highlands and Petaling regions of Peninsular Malaysia.